Estimate the Survival Function of the Power Lomax (POLO) Distribution by Using the Simulated Annealing Algorithm - A. Al-Saaedy, Mustafa; H. Aboudi, Emad (Al-Nahrain Journal of Science, 2022)
In this paper the survival function of the Power Lomax distribution is estimated by two methods of estimation, which are the maximum likelihood method and the moment method. The obtained estimators contain non-linear equations that cannot be solved by ordinary mathematical methods and do not represent the estimations clearly, so a simulated annealing algorithm was used to solve this problem, then simulation was used to compare the estimation methods based on the statistical comparison criterion mean squares of integral error (IMSE) and to get the best estimator for survival function. The results show the preference the maximum likelihood method than the moment method.